Permohonan Isbat Nikah Bagi Poligami yang Tidak Dicatatkan - Murni, Murni; Nisa, Mega Naurin (Trunojoyo Madura University, 2023)
This research aims to examine the basic reasons for the judge's consideration of granting marriage isbat requests to unregistered polygamists. Is it appropriate for a judge to grant a request for isbat for a polygamous marriage that has not yet completed the administrative requirements. Types of normative legal research with a statutory approach. The results of the research show that the judge's consideration in the Religious Court Decision Number 161/PDT.G/2014/PA.TLG in granting the request for isbat marriage to polygamy was correct, but the judge ignored the administrative requirements that must be fulfilled by applicants for marriage isbat. In terms of procedures, there is no difference between polygamous marriage isbat and non-polygamous marriage isbat. However, the polygamy agreement has additional conditions. For this reason, Religious Court judges in their considerations must look at the fulfillment of these additional conditions as a basis for granting a request for marriage isbat for polygamy.